2016
DOI: 10.17532/jhsci.2016.266
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles in nursing management: implications for staff outcomes

Abstract: Introduction: Nursing is a people-centred profession and therefore the issue of leadership is crucial for success. Nurse managers’ leadership styles are believed to be important determinant of nurses’ job satisfaction and retention. In the wake of a global nursing shortage, maldistribution of health workforce, increasing healthcare costs and expanding workload, it has become imperative to examine the role of nurse managers’ leadership styles on their staff outcomes. Using the Path-Goal Leadership theory as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
3
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 31 publications
8
69
3
4
Order By: Relevance
“…More than half 51.7% of the nursing staff intended to leave their current workplaces, and 20% of them were actively seeking the opportunities to leave. The nurse managers' leadership styles statistically explained 13.3% of the staff intention to stay at their current job position (Asamani, Naab, & Ofei, 2016).…”
Section: The Impact Of Leadership On Subordinatesmentioning
confidence: 99%
“…More than half 51.7% of the nursing staff intended to leave their current workplaces, and 20% of them were actively seeking the opportunities to leave. The nurse managers' leadership styles statistically explained 13.3% of the staff intention to stay at their current job position (Asamani, Naab, & Ofei, 2016).…”
Section: The Impact Of Leadership On Subordinatesmentioning
confidence: 99%
“…These efforts have not only resulted in Ghana being cited as a country on a good footing towards UHC but also as a leading producer of physicians, nurses and midwives in sub-Saharan Africa [10]. Nonetheless, some reports and published literature assert that Ghana's HRH stock may not be optimal and is plagued with inefficient distribution [11][12][13][14]. For instance, Scheffler et al [14] showed a serious deficit in the number of physicians, nurses and midwives in Ghana by 2015 which later estimates puts at 42% gross deficit in HRH availability but much worse amongst specialised groups of health professionals [15].…”
Section: -2021 and Earlier Ones) Are All Geared Towards Ensuring Univmentioning
confidence: 99%
“…Burnout merupakan gejala kelelahan fisik, emosional dan mental dengan perasaan rendahnya harga diri akibat stres yang berkepanjangan. Berbagai penelitian di Indonesia melaporkan tingginya burnout dikalangan perawat dengan prevalensi yang berkisar antara 38% -75 % (Aulia, 2018) , (Awalia, 2013), (Prestiana & Purbandini, 2012), (Asamani, Naab, Maria, & Ofei, 2016) , (Mariyanti & Citrawati, 2011), (Ningrum, 2014), (Eliyana, 2016), (Wati, 2017). Penelitian di luar negeri juga menunjukkan tingkat burnout yang tinggi dengan prevalensi 22%-98% sejak tahun 2013 sampai 2017 (Dolan et al, 2015), (Vargas, Can, Can, & De, 2015), (Frey, Robinson, Wong, & Gott, 2018), (Font, Corti, & Berger, 2015), (Britt, Koranne, & Rockwood, 2017).…”
Section: Latar Belakangunclassified
“…Upaya untuk meminimalkan burnout antara lain meningkatkan kecerdasan emosional, koping individu, spiritualitas, hubungan dengan rekan kerja, serta meningkatkan aspek kepemimpinan perawat (Maslach et al, 2001), (Patrick, Wagga, Wales, Lavery, & Campus, 2007), (Scaufeli & Janczur, 2004), (Gentene, 2013) , (Hunsaker, 2013). Salah satu gaya kepemimpinan yang sesuai dalam menghadapi perubahan, meningkatkan pro aktif bawahan dan membuat bawahan lebih merasa dihargai dan lebih menyentuh faktor emosional adalah gaya kepemimpinan transformasional (Asamani et al, 2016) , (Hartiti, 2013), (Afandi, 2013). Gaya kepemimpinan transformasional memberikan sentuhan emosional yang lebih baik untuk perawat dan hal ini akan mempengaruhi tingkat burnout perawat.…”
Section: Latar Belakangunclassified